Capabilities and Operational Performance: Case Study in Automotive Supply Chain - Alexandre Tadeu Simon; Eliciane Maria Silva; Renan Stenico Campos; Eliacy Cavalcanti LÃ©lis (International Journal of Supply Chain Management, 2019)
Sharing of operational capabilities in the supply chains brings benefits to the companies involved. However, studies on operational capabilities in the Brazilian supply chain are still non-existent. The current article investigates the effects of operational capabilities on operational performance in the automotive supply chain. An explanatory cross-section survey was employed. The sample used concentrates on the southeast region of Brazil where there is the largest concentration of automakers. Employing the Exploratory Factor Analysis (EFA) and regression analysis, the results show that three operational capabilities have positive and significantly operational performance. These operational capabilities are cooperation, improvement and customization.